ANALISIS PENGARUH BRAND IMAGE, PRICE PERCEPTION, DAN SERVICE QUALITY TERHADAP CUSTOMER LOYALTY PADA PELANGGAN URBAN KITCHEN - Timothy Joshua; Eddy Haryadi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2014)
This study was conducted to determine the influence of Brand Image, Price Perception, and Customer Service Qualityon Customer Loyalty in Urban Kitchen. The questionnaires were distributed to 150 respondents in four locations of Urban Kitchen employing simple random sampling technique. The data obtained were processed and analyzed using the Structural Equation Model (SEM) with LISREL8.72. The results indicate that Brand Image and Service Quality have significant influences on Customer Loyalty, while Price Perception does not influence Customer Loyalty.